AN UNUSUAL FOREIGN BODY IN TRACHEA - Musani, Mohammad Ayub; Khambaty, Yousuf; Jawed, Itrat; Khan, Faheem Ahmed; Ashrafi, Khalid A. (Journal of Ayub Medical College Abbottabad, 2010)
We report a very unusual case of foreign body (FB) in the tracheo-bronchial tract of a male child, who presented to us in the Emergency Department at our tertiary care centre with the complaint of FB in throat, cough bouts and choking sensation with pain and difficulty in breathing for whom an emergency rigid endoscopy was carried out after appropriate investigations. Keywords: Foreign body, tracheo-bronchial tract, management, unusual